STUDY THE EFFICACY OF PRATISARAN AGNIKARMA IN THE MANAGEMENT OF KADARA W.S.R. TO CORN (AYUSHDHARA, 2018)
Ayurveda is the ancient system of health-care and longevity. It involves a holistic view of man, their health and illness. It is the source of divine knowledge which has enlightens the path of complete solace since edges. Man, the superior most of all the species is always remaining in search of one primary goal i.e. normal health from Vedic era to space age. All the researches have been directed by eminent scholars to achieve the same.In modern science even though there are varieties of modalities aiming at cure of corn viz. soft shoes and soft pads at the pressure points of sole, Salicylic acid, Corn cap, Surgical excision etc. But none of them are complete and devoid of recurrence. Corn has a notorious tendency to recur after excision.Acharya Sushruta has earmarked that the disease which is not cured by Bhaishajya, Kshara and Shastra those diseases markedly cured by Agnikarma procedure. In our present study we had taken 60 patients, in two groups, 30 patients in each group. The first group is experimental group i.e. Pratisaran Agnikarma and second is control group i.e. excision of corn. We have taken observations viz., age, sex, occupation, weight, nature of work, use of footwear etc., by which we can observe the characteristics of disease in these conditions. To assess the nature of disease we have taken assessment criteria like Vedana (pain), elevation, hyperkeratosis, Spershasahatva (tenderness), ulceration, discharge and consistency. From above criteria we made the result of effectiveness of treatment by using Wilcoxon signed rank test and Mann Whiteny’s U test on 0.001% level of significance and it was concluded that Pratisaran Agnikarma acts as Shulahara, Lekhana, Chedana, Bhedana and para surgical on Kadara.